Passive acoustic monitoring data recorded by recorder SV1058 at mooring AWI231-11 in the Weddell Sea, Southern Ocean, from 2014 to 2016 - Karolin Thomisch; Stefanie Spiesecke; Katharina Lefering; Ramona Mattmüller; Ilse Van Opzeeland; Sarah Zwicker; Olaf Boebel (PANGAEA, 2024)
Passive acoustic monitoring (PAM) data were collected by recorder SV1058 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 66.5118° S, 0.0252° W, mooring AWI231-11, in the Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from December 2014 to December 2016, passive acoustic data were collected from December 2014 to May 2016 (recording period) by SV1058 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 973 m depth and scheduled to record continuously at a sample rate of 6,857Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 2+ (see Data Processing Report), deviating from Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).